ANALISIS RANTAI NILAI MINYAK KELAPA (CCO, CRUDE COCONUT OIL) DI KECAMATAN SINONSAYANG KABUPATEN MINAHASA SELATAN - Helena ., Kelyombar; Nordy F. L. Waney; Tommy F. Lolowang (AGRI-SOSIOEKONOMI, 2018)
The purpose of this study was to determine the Coconut Oil Product Value Chain (CCO) in Sinonsayang District, South Minahasa Regency. Analysis of the coconut oil product value chain (CCO), there are several actors involved in the core process of the coconut oil product value chain (CCO) in Sinonsayang District and form a chain that has value. The actors involved included copra farmers, intermediary traders and PT. Cargill. The study lasted for 3 (three) months starting from June 2018 to August 2018 in Sinonsayang District, South Minahasa Regency. The data used are primary data obtained through interviews with 15 copra farmers, 5 brokers and PT. Cargill as a coconut oil (CCO) company. Secondary data was obtained from the Sinonsayang Sub-District Office and agencies related to research. The analysis used is using quantitative tools through cost and margin approaches. The results showed that the copra produced by farmers was 5,041 kg with a raw material of 20,165 coconuts. With the selling price of copra amounting to Rp.7,500 / kg and the value received by farmers is Rp.37,809,375. The trader buys copra raw material from the farmer as much as 5,041 kg then sells to the company as much as 5,083 kg at the price of 8,500 / kg and the value received by the trader is Rp.42,832,000. The company buys copra raw material from the trader as much as 5,083 kg. From copra raw material, the company produces crude coconut oil (CCO) of 3,527 kg and 1,007 Kg cake then exports the CCO at a price of Rp. 23,000 / kg and offers a price of Rp. 3,000 / kg value of Rp.84,134,600 . Each value chain actor obtains a margin that is in accordance with the effort made. * jnkd *.